The Effect of Service Quality on Customer Satisfaction at Asrin Cafe in Langkat - Arini, Rizky Mega; Rahmi, Audina; Sinaga, Ananda Sabrida Tora Boru; Muthmainnah, Riyadatul; Hidhayati, Annisa Tri (PT Mattawang Mediatama Solution, 2025)
This study investigates the effect of service quality dimensions-tangibility, reliability, responsiveness, assurance, and empathy on customer satisfaction at Asrin Cafe in Langkat, North Sumatra. Using a sample of 30 respondents, data were collected via questionnaires and analyzed through multiple linear regression with SPSS. The findings reveal that responsiveness and empathy significantly influence customer satisfaction, while the other dimensions do not exhibit individual significance. However, jointly, all five dimensions positively and significantly impact customer satisfaction. The adjusted R-square of 0.522 indicates that service quality accounts for 52.2% of the variance in customer satisfaction. This study underscores the critical role of responsiveness and empathy in enhancing service experiences.